Standard system of design and maintenance of road structures/Kelių statinių projektavimo ir priežiūros normatyvinių dokumentų sistema - Kamaitis, Zenonas (Journal of Civil Engineering and Management, 2001)
Bridges are designed, constructed and maintained. All these activities are closely interrelated and the codes and standards must therefore concern all these activities. Guidance on all these activities exists in various countries in the form of standards, guides, and recommendations. European standards are currently being developed. In some countries as well as in Lithuania European Standards have to be adopted to suit local traditions and conditions. National application documents will give details of compatible supporting standards to be used. Lithuanian normative document system includes Regulations (STR), Code of Practices (ST), Standards (LST), and Recommendations (SR). All these documents are intended for guidance in planning, designing, execution, maintenance, inspections, repair or reconstruction of road and railway bridges. Codes and Standards have to ensure that road structures designed and constructed maintain their required performance for a sufficiently long period of time, which is expected to be 100 years, assuming that an appropriate level of workmanship and maintenance is achieved. The Structural Euro-codes comprise a group of standards for the structural and geotechnical design of buildings and civil engineering works. Eurocodes and supporting European standards published by CEN will replace existing national codes and standards. Although two aspects have to be taken in consideration: – European codes do not cover all design situations and they are under development. – Each country may introduce modifications according to local conditions and traditions. Proposals for development of national code system for design and maintenance of road structures are presented (see Fig). Including especially durability and assessment of existing bridges into structural life cycle design and into standards and practical guides is of vital importance. To achieve this the additional prenormative research is required. The well-prepared standard system should improve the quality and reliability of new and existing road structures in Lithuania. Article in Lithuanian. First Published Online: 30 Jul 2012